2023
DOI: 10.1186/s13075-023-03044-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomic screening uncovers candidate diagnostic and monitoring serum biomarkers of ankylosing spondylitis

Abstract: Background We sought to discover serum biomarkers of ankylosing spondylitis (AS) for diagnosis and monitoring disease activity. Methods We studied biologic-treatment-naïve AS and healthy control (HC) patients’ sera. Eighty samples matched by age, gender, and race (1:1:1 ratio) for AS patients with active disease, inactive disease, and HC were analyzed with SOMAscan™, an aptamer-based discovery platform. T-tests tests were performed for high/low-dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
0
0
0
Order By: Relevance
“…18 Previous studies have shown elevated complement activation (ie, soluble MAC) in axSpA 25 ; others have found complement proteins (C5, C6 and C9) to be upregulated in proteomic analysis and serve as potential biomarkers for both diagnosis and disease activity in r-axSpA. 26 We have previously identified the complement lectin pathway PRM L-ficolin as a potential axSpA biomarker in a cohort of Danish patients with axSpA. 27 28 The current study investigated the diagnostic potential in a larger cohort of newly diagnosed, ts/bDMARD-naïve axSpA patients compared with clinically relevant controls suffering from other causes of chronic low back pain (cLBP).…”
Section: Rmd Open Rmd Open Rmd Openmentioning
confidence: 99%
“…18 Previous studies have shown elevated complement activation (ie, soluble MAC) in axSpA 25 ; others have found complement proteins (C5, C6 and C9) to be upregulated in proteomic analysis and serve as potential biomarkers for both diagnosis and disease activity in r-axSpA. 26 We have previously identified the complement lectin pathway PRM L-ficolin as a potential axSpA biomarker in a cohort of Danish patients with axSpA. 27 28 The current study investigated the diagnostic potential in a larger cohort of newly diagnosed, ts/bDMARD-naïve axSpA patients compared with clinically relevant controls suffering from other causes of chronic low back pain (cLBP).…”
Section: Rmd Open Rmd Open Rmd Openmentioning
confidence: 99%